SERTULUM DIPTEROCARPACEARUM MALAYENSIUM-VI - D. F. VAN SLOOTEN (Research Center for Biology, 1956)
The genus Balanocarpus has been regarded as distinct by reason of its calyx lobes, which do not exceed the wooden nut but which enclose the very base of it,forming a five-lobed wooden cup by the equally though slightly enlarged strongly imbricate segments of the flowering calyx.Symington has called particular attention to the fact that it seemed to lack natural generic characters,viz.satisfactory and sharply marked distinctions from other groups, as was already superficially realised by his predecessorsIn agreement with earlier suggestions by Symington, Balanocarpus is.given up,it being an artificial genus.Many of its species are referable to Shorea.Of the latter,12 species are treated,7 of which are described as new.Editor's Note.-Dr D. F. van Slooten was steadily continuing his revision of the Dipterocarpaceae when his untimely death put a stop to this most useful and painstaking task. During the last few years of his life I had the privilege to be consulted by Dr van Slooten regarding certain aspects of his work and this has made me somewhat familiar with the present paper and some of its problems. As this valuable contribution was not yet ready for the press, I ventured to put it into a definite shape to make it available rather than to leave it unpublished. Therefore, the errors that it may contain are wholly my own responsibility.-M. A. Donk.